2020
DOI: 10.1111/pce.13826
|View full text |Cite
|
Sign up to set email alerts
|

Allometric co‐variation of xylem and stomata across diverse woody seedlings

Abstract: Leaf stomatal density is known to co-vary with leaf vein density. However, the functional underpinning of this relation, and how it scales to whole-plant water transport anatomy, is still unresolved. We hypothesized that the balance of water exchange between the vapour phase (in stomata) and liquid phase (in vessels) depends on the consistent scaling between the summed stomatal areas and xylem cross-sectional areas, both at the whole-plant and single-leaf level. This predicted size co-variation should be drive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 37 publications
1
15
0
Order By: Relevance
“…Species names were verified according to www.theplantlist.org , https://powo.science.kew.org/ and www.iwgs.org . In 2020, at least ten healthy similar-sized mature floating leaves with petioles of similar size were collected for 26 species to determine leaf stomatal and petiole vascular traits following Zhong et al (2020) . In 2021, an additional five floating-leaved plants were collected and measured.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Species names were verified according to www.theplantlist.org , https://powo.science.kew.org/ and www.iwgs.org . In 2020, at least ten healthy similar-sized mature floating leaves with petioles of similar size were collected for 26 species to determine leaf stomatal and petiole vascular traits following Zhong et al (2020) . In 2021, an additional five floating-leaved plants were collected and measured.…”
Section: Methodsmentioning
confidence: 99%
“…construction of stem vs. leaf) during the process of water transport, which has shaped the evolution of plant function across vascular plants ( Enquist, 2002 , 2003 ; Coomes et al , 2008 ; Carins et al , 2014 ; Wen et al , 2020 ). For example, Zhong et al (2020) found that the balance of water exchange between liquid and gas phases depended on the consistent scaling between leaf total stomatal area and stem xylem area in seedlings of woody terrestrial species. Allometric relationships between photosynthetic, autotrophic tissues (e.g.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, understanding of hydraulic‐stomatal coordination in seedlings has been fragmentary, especially for only few months old plants. Seedlings of different species 3 wk after the opening of the first leaf show remarkable co‐variation in xylem and stomatal anatomical traits (Zhong et al ., 2020). Accordingly, also a strong coordination in physiological parameters might be expected.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, stomata are separated by various shapes, sizes, and numbers of intervening cells (including epidermal cells and subsidiary cells) in a particular arrangement on the leaf surface (Carpenter, 2005). Stomata are developmentally coordinated with mesophyll (Baillie and Fleming, 2020) and xylem (Brodribb et al, 2017;Zhong et al, 2020), and various plants break this "rule" and produce stomata arranged in clusters, which reduce water loss from plant leaves due to neighboring stomata interfere with each other (Franks and Casson, 2014;Lehmann and Or, 2015). In comparisons of high and low clustering genotypes that have similar stomatal density and size, operational stomatal conductance was consistently lower in lines with highly clustered stomata, and stomatal clustering was shown to significantly reduce carbon assimilation (Dow et al, 2014; Supplementary Figure 1).…”
Section: Introductionmentioning
confidence: 99%